The Natural Course of Pancreatic Cysts in Inflammatory Bowel Disease: Results of a Long-term Follow-up. Issue 7 (August 2022) - Abou Saleh, Mohannad; Alkhayyat, Motasem; Habash, Alaa; Almomani, Ashraf; Qayyum, Farhan; Kim, Woan; Bena, James; Martin, Charles; Regueiro, Miguel; Rieder, Florian; Simons-Linares, Carlos Roberto; Chahal, Prabhleen
Abstract : Objectives: The natural course of pancreatic cysts in inflammatory bowel disease (IBD) is unknown. We aim to describe the natural course of pancreatic cysts in IBD and evaluate long-term outcomes. Methods: A database of patients with abdominal imaging diagnosis of pancreatic cysts (2008–2019) was reviewed. Patients with IBD and pancreatic cysts (study group) and pancreatic cysts without IBD (controls) were selected. Outcomes were measured at 1, 3, 5, and 10 years. Several logistic regression models were used for analysis. Results: Of the 1789 patients evaluated, 1690 had pancreatic cysts without IBD, and 78 had IBD and pancreatic cysts. Majority of cysts were intraductal papillary mucinous neoplasms. Patients with IBD and pancreatic cysts were more likely to be diagnosed with pancreatic cysts at a younger age ( P < 0.001) and were more likely to undergo surgical intervention at a younger age ( P < 0.001). Conclusions: This is the first study to evaluate the natural course of pancreatic cysts in IBD patients. Patients with IBD were more likely to have pancreatic cysts detected at a younger age. Despite the early presentation, there were no differences in long-term outcomes. Patients with IBD with pancreatic cysts should be managed similarly to those without IBD.